As unidades heterogenéricas em dicionários bilíngues de espanhol para aprendizes brasileiros: análise do tratamento lexicográfico - Fioravanti, Sueli Cabrera [UNESP] (2015)
The objective of this research is to analyze the lexicographical treatment given to a set of heterogeneric lexical units in the microestructure of Portuguese-Spanish School Dictionaries for Brazilian learners. Heterogeneric lexical units are those which have the same or similar spelling, but different genres in each of the two languages considered. The heterogenerics are the object of study of this work, mainly because in the Spanish language learning process Brazilians usually find these words difficult to learn and use, especially in the speaking and writing production. When expressing themselves in Spanish, Brazilian learners often make mistakes in the use of noun genders. This study was conducted by selecting a sample of heterogeneric lexical units in a corpus composed by different text genres from Spanish language teaching textbooks, more specifically from three Spanish teaching collections pre-selected by the PNLD (National Textbook Program) 2011/2012. This research is based on the theories and practices of Bilingual Pedagogical Lexicography and Corpus Linguistics and it focused on analyzing how the lexicographical information is presented to serve as a support for the learning of heterogenerics nouns in Spanish by Brazilian learners. The results indicate that the bilingual dictionaries analyzed, generally do not have enough information to assist the learner in the learning process regarding heterogeneric lexical units